PENERAPAN ALGORITMA C4.5 UNTUK PREDIKSI PENYAKIT HEPATITIS - Wisti Dwi Septiani (Jurnal Techno Nusa Mandiri, 2014)
Hepatitis is an inflammation disease of the liver because an infection that attacks and causes damage to cells and liver function. Hepatitis is a disease precursor of liver cancer. Hepatitis can damage liver function as neutralizing poisons and digestive system in the body that break down nutrients and then spread to all organs of the body that very important for humans. Research on predicting disease hepatitis have been carried out by previous researchers. This research using the method of classification data mining algorithm C4.5. The measurement method using cross-validation, confusion matrix, and ROC curve. The result of this research is a decision tree rule with 77.29% accurate.